Low-virulence phylogenetic background of CTX-M-producing Escherichia coli isolated from extraintestinal infections - Paiva, Andyara L.; Lincopan, Nilton; Silva, Ketrin C; Neves, Patrícia R; Moreno, Andrea M; McCulloch, John A; Astolfi-Ferreira, Claudete S; Ferreira, Antonio JP (The Journal of Infection in Developing Countries, 2013)
This item has no abstract. Follow the links below to access the full text.